The invention of a “school sceptical” pyrrhonist and radical - Román Alcalá, Ramón (Revista de Filosofía, 2012)
The history of skepticism is obscure and confusing. While recognizing the existence, mysterious and controversial, a Platonic academic skepticism, there are some doubts about the reality of a school Pyrrhonist unequivocal radical. In this article we will discuss, first, to what extent can we speak of school, sect or philosophical group Pyrrhonian, and second, if, as we shall see, no doubt recognizing this homogeneous group why it is spoken of as ‘school’, or ‘system’ ‘secta’ Pyrrhonian?